Seamless Transition between Islanded and Grid Connected Three-Phase VSI-based Microgrids - Khan, M. H.; Pathan, E.; Asad, M.; Sadiq, M. A.; Qureshi, A. A.; Shahid, M.; Pathan, A. K.; Shaikh, N. I. (Engineering, Technology & Applied Science Research, 2021)
Microgrids (MGs) are the emergent solution to overcome the current electricity demand. The MGs provide the facility to operate in both isolated and grid-connected modes. For both operating modes, Distributed Generation (DG) inverters are operating under grid forming or grid following control modes. During mode switching, the MG experiences enormous fluctuations, which occur due to the unidirectional islanding event. This paper presents a control strategy by using the modified power control scheme, current controller, and DC linked voltage controller scheme to ensure the operational mode transfer smoothly from the grid-connected to the islanded mode and vice versa. The proposed control scheme is applied to a three-phase distributed energy resource-based MG system with fixed loads. The simulation results validate the effectiveness of the control technique while tested at the point of common coupling and also at the time of mode transfer.